Critical and Creative Education in Hadith: Global Challenges - Syaridawati; Ismail , La Ode Ahmad; Sakka, Abbdul Rahman (Golden Ratio of Data in Summary, 2025)
In the face of increasing global interconnectedness, education systems are under growing pressure to cultivate learners equipped with critical and creative thinking skills. This study investigates the relevance and application of prophetic Hadiths in developing educational models that address the challenges of globalization. Utilizing a qualitative-descriptive method, the research analyzes selected Hadiths that emphasize the importance of lifelong learning, rational inquiry, openness to diverse knowledge, and personal transformation. Through thematic content analysis, three key themes emerge: the promotion of lifelong intellectual engagement, the imperative for critical self-transformation, and the embrace of global knowledge horizons. These principles, embedded within the Hadith tradition, resonate with 21st-century educational goals, including adaptability, ethical reasoning, and interdisciplinary literacy. The findings reveal that the teachings of Prophet Muhammad (peace be upon him) offer not only spiritual guidance but also foundational educational insights that align with modern pedagogical frameworks. Theoretically, the study contributes to the integration of Islamic epistemology with global education theory, enriching the discourse on critical pedagogy through a faith-based lens. Managerially, it offers actionable implications for curriculum development, teacher training, and educational leadership particularly within Muslim-majority contexts by advocating for a balanced approach that unites tradition and innovation. Ultimately, this research affirms that Hadith-based education can serve as a strategic response to global challenges, fostering learners who are not only intellectually competent but also morally grounded and globally conscious.